Barriers and Enablers to effective science-policy interfacing for CSA mainstreaming: lessons learnt from the science-policy platforms in West Africa - Segnon, Alcade C; Botchway, Vincent Ansah; Samaké, Oumar; Idrissa, Mamoudou; Essegbey, George Owusu; Karbo, Naaminong; Sogoba, Bougouna; Whitbread, Anthony M.; Thornton, Philip K.; Zougmoré, Robert B. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
This Info Note provides a synthesis of barriers and enablers of effective science-policy interfacing using the cases of the national science-policy dialogue platforms in Ghana, Mali and Niger. Using a participatory SWOT analysis, the study analyzed the strengths, weaknesses, opportunities and threats to the platforms’ effectiveness and sustainability across the three countries. The synthesis of the analysis provides an overview of factors that could limit or facilitate effective science-policy engagement in West Africa